Effects of actions preceding the jump shot on gaze behavior and shooting performance in elite female basketball players - Oudejans, R. R. D.; Karamat, R. S.; Stolk, M. H. (International Journal of Sports Science and Coaching, 2012)
The aim was to investigate the effects of different actions preceding the jump shot on basketball shooting in expert female basketball players. Participants took two-point jump shots after a dribble or after receiving a pass. The dribble was executed with the dominant or non-dominant hand. Similarly, the pass was received from the side of the dominant or nondominant hand. Shooting percentages were higher after a pass than after a dribble, and after a dominant-side than after a non-dominant-side preaction. Higher percentages were accompanied by longer execution times of actions preceding the shot. Furthermore, it appeared that in all conditions players looked at the rim sufficiently long for accurate shooting. We conclude that actions preceding the jump-shot affect shooting percentages. Effects are related to execution time of actions prior to the shot, possibly in combination with the biomechanical consequences of performing these actions on the dominant or non-dominant side.